2019
DOI: 10.3389/fpsyg.2019.02640
|View full text |Cite
|
Sign up to set email alerts
|

Moral Leadership and Unethical Pro-organizational Behavior: A Moderated Mediation Model

Abstract: In this paper, we aim to examine the indirect effects of moral leadership on unethical pro-organizational behavior (UPB). Drawing on Social Identity Theory, identification with supervisors (social identity) and taking responsibility (personal identity) were hypothesized as mediators linking moral leadership and UPB. In addition, we aim to investigate the moderating role of moral courage in the relationship between moral leadership and UPB. We conducted two studies with two distinct samples: one on a sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 83 publications
2
35
2
Order By: Relevance
“…It goes in line with McCown (2010) stating that students have few opportunities to obtain the first-hand experience of leadership in the field and they need the framed situations to gain experience of decision-making and risk-taking in safe conditions. It also agrees with the previous research conducted by Enlow and Popa (2008) and Yujuan and Hai (2019) revealing the importance of ethics and moral in leadership and considering imagination a key skill. The results obtained in the study are also consistent with views of the developers of the degree programmes for the British Army at Henly Business School (it can be accessed via the link: https://www.henley.ac.uk/news/2017/ahep).…”
Section: Discussionsupporting
confidence: 92%
“…It goes in line with McCown (2010) stating that students have few opportunities to obtain the first-hand experience of leadership in the field and they need the framed situations to gain experience of decision-making and risk-taking in safe conditions. It also agrees with the previous research conducted by Enlow and Popa (2008) and Yujuan and Hai (2019) revealing the importance of ethics and moral in leadership and considering imagination a key skill. The results obtained in the study are also consistent with views of the developers of the degree programmes for the British Army at Henly Business School (it can be accessed via the link: https://www.henley.ac.uk/news/2017/ahep).…”
Section: Discussionsupporting
confidence: 92%
“…The author's argument hung on objectivity of universal moral principles as the legitimate basis of a sound understanding of moral leadership. Wang and Li (2019) examined the indirect effects of moral leadership on unethical proorganisational behavior. In the study that included 161 MBA students and 205 enterprise employees in china, and using structural equation modeling, the authors found identification with supervisors, taking responsibility, and moral courage as mediating relationship between moral leadership and unethical pro-organisational behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Morality boosts team identification owing to two major reasons. First, moral leaders demonstrate moral principles and responsibility as norms and behavioral codes for team members to place on their own actions, thus shaping their collective self-concepts (Y. Wang & Li, 2019).…”
Section: Theory and Development Of Hypothesesmentioning
confidence: 99%